(untitled) (Research, Society and Development, 2020)
Introduction: Pain during local anesthetic injection is one of the main problems in most of dental procedures, and a technique to prevent this situation is the previous use of topical anesthetics. Among these, the most commonly used agent worldwide is 20% benzocaine, although it has a limited potency and short length. Thereby, topic anesthetics based on a eutectic mixture of 2,5% lidocaine and 2,5% prilocaine (5% EMLA) have shown promising clinical results in medicine and dentistry. The pharmacological and psychological effects in pain control due to topical anesthetics has been fairly studied. However, the reports in literature are contradictory. Objective: To compare de efficacy of 20% benzocaine and 5% EMLA in pain reduction during infiltrative anesthesia, therefore to determine if they have a pharmacological effect or if its action it’s due to psychological effect. Materials and methods: A literature review was done using PubMed data base and it was selected 8 articles from 2003 to 2019. Results: There is not a consensus towards 20% benzocaine efficacy as a topical agent and your action was only observed in one study. On the other hand, EMLA showed to be superior to benzocaine and placebo in all the analyzed studies, proving its pharmacological effect. Conclusion: It’s clear a superiority of 5% EMLA efficacy as a topical anesthetic when compared to 20% benzocaine and placebo.